Sisters' Muffled Voice: A Feminist Reading of Edith Wharton’s Bunner Sisters and Taha Husain's The Call of The Curlew - Shaalan, Ban (Al-Adab Journal, 2025)
The present paper offers a comparative feminist reading of the American novelist Edith Wharton and the Egyptian novelist Taha Husain. It aims at analyzing both Wharton’s Bunner Sisters (1916) and Husain’s The Call of The Curlew (1934/1980) in terms of feminist criticism demonstrated in Beauvoir’s theory of patriarchy in her book: The Second Sex (2010). The analysis of these novellas provokes three substantial points regarding the artistic achievement of both writers. First, patriarchy is a male programming intended to subdue and decentralize the female by treating them as a sexed being, or rather as an inessential other. Second, the inferior position of women inspires Wharton and Husain to incorporate Beauvoir’s theory of patriarchy into their fictional works. To attain such an aim, both writers start narrative visions through which they expose patriarchal methods to marginalize and subordinate women. Lastly, the close reading of the novellas shows that they reflect the systemized oppression of women. Such is the shared leitmotif of Wharton and Husain’s narrative.